2003
DOI: 10.1002/adma.200305425
|View full text |Cite
|
Sign up to set email alerts
|

A Single Photochromic Molecular Switch with Four Optical Outputs Probing Four Inputs

Abstract: Many researchers have considered how to exploit molecular properties, with their intrinsic diversity, to create molecular switches. The use of photochromic compounds, such as spiropyran and diarylethene, as photoswitching systems attracts much attention because of their potential ability for application in photonic devices, where each isomer of the photochromic compound can represent ª0º or ª1º of a digital binary code.[1] Raymo and Giordani [2] demonstrated the modulation of pyrene fluorescence in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(60 citation statements)
references
References 27 publications
0
57
0
3
Order By: Relevance
“…[43,54] This characteristic could be potentially used for the construction of certain optoelectronic devices. [55] Fluorescence switches of 1 Emission intensity changes of diarylethene 1 upon irradiation with UV and visible light (λ≥550 nm) in acetonitrile (5.0×10…”
Section: Crystal Structure and Photochromism In The Crystalline Phasementioning
confidence: 99%
“…[43,54] This characteristic could be potentially used for the construction of certain optoelectronic devices. [55] Fluorescence switches of 1 Emission intensity changes of diarylethene 1 upon irradiation with UV and visible light (λ≥550 nm) in acetonitrile (5.0×10…”
Section: Crystal Structure and Photochromism In The Crystalline Phasementioning
confidence: 99%
“…However, most diarylethene molecules are not appreciably fluorescent. One effective strategy for fluorescence modulation is to combine the diarylethene unit with a fluorophore [11][12][13][14], and the fluorescence of fluorophore can be controlled by external stimuli [15][16][17][18]. In our previous research, we developed a series of diarylethenes with a rhodamine unit and demonstrated their multiple responsive photoswitching properties induced by light, proton, and metal ions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins (CDs) and their derivatives [9][10][11][12] with multi-state switching and multi-responsive properties are ideal candidates for molecular logic storage. Hitherto, a large number of chemical or biological systems performing versatile functions of digital electronic components [13][14][15][16][17][18][19][20][21][22] have been demonstrated in nanoscale spaces or in vivo. However, the utilization of either the stable aggregated or the monomeric conformational species, which are generated by reversible supramolecular assembly and disassembly behavior as addressed media of data storage and logic calculations, is rarely reported.…”
Section: Introductionmentioning
confidence: 99%